Beispiel Nr: 19
$ D_h=\begin{array}{|cc|}a1\ & b1 \\ a2&b2 \\ \end{array}= a1 \cdot b2 -b1 \cdot a2 \\ D_x=\begin{array}{|cc|}c1\ & b1 \\ c2&b2 \\ \end{array}= c1 \cdot b2 -b1 \cdot c2 \\ D_y=\begin{array}{|cc|}a1\ & c1 \\ a2&c2 \\ \end{array}= a1 \cdot c2 -c1 \cdot a2\\ x=\frac{D_x}{D_h} \\ y=\frac{D_y}{D_h} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +1 y =2\\ 3 x +3 y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\ D_h=\begin{array}{|cc|}1\ & 1 \\ 3&3 \\ \end{array}= 1 \cdot 3 -1 \cdot 3=0 \\ D_x=\begin{array}{|cc|}2\ & 1 \\ 3&3 \\ \end{array}= 2 \cdot 3 -1 \cdot 3=3 \\ D_y=\begin{array}{|cc|}1\ & 2 \\ 3&3 \\ \end{array}= 1 \cdot 3 -2 \cdot 3=-3 \\ \ L=\{ \} \, $